The Accounting and Accountability Practices of Fairtrade International (FLO). (1st September 2016) - Semeen, Homaira; Islam, M. Azizul; Quayle, Annette
ABSTRACT: This study examines the accounting and accountability practices of Fairtrade International (FLO), one of the largest Fair Trade umbrella organisations. Our aim is to explore whether new forms of accounting and related disclosures emerge in the reporting practices of FLO and how these reflect their self-declared social mission towards the emancipation and sustainability of producers. Using thematic analysis and reflecting on Bourdieu's theory of symbolic power, we analyse FLO's reporting practices from 2006 to 2013. Our findings reveal that FLO mobilises the taken-for-granted images and symbols of 'fairness' in the Fair Trade system by using descriptive statistics of Fairtrade premium distributions and pictures of producers, but keeps silent to current concerns surrounding the limitations of Fair Trade. Such findings extend important insights into how new forms of accounting and related disclosure are used to legitimise the practice of Fair Trade.